Injury profile in ice hockey from the 1970s through the 1990s in Finland - Molsa, J.; Kujala, U.; Nasman, O.; Lehtipuu, T. P.; Airaksinen, O. (The American Journal of Sports Medicine, 2000)
The aim of this study was to investigate the incidence, types, and mechanisms of injury in Finnish ice hockey players at the highest competition level in different decades. Several teams were observed prospectively during the seasons between 1976 and 1979, and in the 1988 to 1989 and 1992 to 1993 seasons. An injury was defined as any sudden trauma requiring examination and treatment by a physician. The inclusion criteria were the same during the entire study. A total of 641 injuries were recorded. The injury rate per game increased significantly from 54 per 1000 player-hours in the 1970s to 83 per 1000 player-hours in the 1990s. The injury profile in the 1980s and 1990s differed from that in the 1970s. Per 1000 player-years, the rate of contusions as well as of sprains or strains increased significantly with each decade. Checking and unintentional collision with an opponent were common mechanisms of injury throughout the study, and the rate of injury by these mechanisms has continually increased. In conclusion, we suggest that there has been an increase in rough body contact between players, causing an alarming increase in the rate of ice hockey injuries.